Synthesis of cyclic β-1,6-oligosaccharides from glucosamine monomers by electrochemical polyglycosylation - Rahman, Md Azadur; Endo, Hirofumi; Yamamoto, Takashi; Okushiba, Shoma; Sasaki, Norihiko; Nokami, Toshiki (Beilstein journal of organic chemistry, 2024)
The synthesis of protected precursors of cyclic β-1,6-oligoglucosamines from thioglycosides as monomers is performed by electrochemical polyglycosylation. The monomer with a 2,3-oxazolidinone protecting group afforded the cyclic disaccharide exclusively. Cyclic oligosaccharides up to the trisaccharide were obtained using the monomer with a 2-azido-2-deoxy group.